Radial bone graft usage for nasal septal reconstruction - Yakup Cil; Atacan Emre Kocman; Abdul Kerim Yapici; Serdar Ozturk (Indian Journal of Plastic Surgery, 2011)
Background: Although various techniques have been described for correction of crooked and saddle nose deformities, these problems are challenging with high recurrence and revision rates. Conventional septal surgery may not be adequate for nose reconstruction in crooked and saddle nose deformities. Materials and Methods: Between December 2005 and October 2009, six patients with crooked nose and five patients with saddle nose deformities underwent corrective surgery in our clinic. All patients were male, and the mean age was 21 years (range, 19-23 years). We used rigid radial bone graft to prevent redeviation and recurrence following corrective nasal septal surgery. Results: The mean follow-up period was 28 months, ranging from 18 to 46 months. Mean operation time was 4 hours (3-4.5). All patients healed uneventfully. None of the patients required secondary surgery. Conclusions: We believe that radial bone grafts offer a long lasting support in treatment of challenging cases with crooked and saddle nose deformities.